2020
DOI: 10.1021/acsami.0c07503
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Triggered Sequentially Responsive Nanocarriers Amplified Cascade Synergistic Effect of Chemo-Photodynamic Therapy with Inspired Antitumor Immunity

Abstract: A desirable cancer therapeutic strategy is supposed to have effective ability to not only exert maximum anticancer ability but also inspire antitumor immunity for preventing tumor relapse and metastasis. During this research, multifunctional upconversion nanoparticles (UCNPs) coated by ROS-responsive micelles are prepared for tumor targeting and near-infrared (NIR)-triggered photodynamic therapy (PDT)-combined synergistic effect of chemotherapy. Moreover, both PDT and chemotherapy agents could activate antitum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
(80 reference statements)
1
37
0
Order By: Relevance
“…However, both chemotherapeutic drugs and A2AR antagonists have limited tumor-targeting ability after intravenous administration, which often induces undesirable adverse effects and unsatisfactory efficacy. Smart nanoparticle drug delivery system is an effective way to alter biodistribution of drugs and achieve spatiotemporally controlled drug release, which is beneficial for improving treatment safety and efficacy 8,[21][22][23] . Significantly, thermal-sensitive drug delivery system has attracted much attention; hyperthermia stimuli at the tumor site can accelerate the drug release from nanoparticles to achieve precise therapy, and on the other hand, hyperthermia itself can also suppress tumor growth 24,25 .…”
mentioning
confidence: 99%
“…However, both chemotherapeutic drugs and A2AR antagonists have limited tumor-targeting ability after intravenous administration, which often induces undesirable adverse effects and unsatisfactory efficacy. Smart nanoparticle drug delivery system is an effective way to alter biodistribution of drugs and achieve spatiotemporally controlled drug release, which is beneficial for improving treatment safety and efficacy 8,[21][22][23] . Significantly, thermal-sensitive drug delivery system has attracted much attention; hyperthermia stimuli at the tumor site can accelerate the drug release from nanoparticles to achieve precise therapy, and on the other hand, hyperthermia itself can also suppress tumor growth 24,25 .…”
mentioning
confidence: 99%
“…Results also indicated that chemo-PDT treatment was effective in inhibiting tumor metastasis in lungs with an increased proportion of CD4 + , CD8 + T lymphocytes in a 4T1 murine model. 45 …”
Section: Combination Of Pdt With Icd-based Therapymentioning
confidence: 99%
“…The ICD process mainly has adenosine triphosphate (ATP) secretion, heat shock protein (HSP)-antigen peptide complex, calreticulin (CRT) surface exposure, and release of high migration protein B1 (HMGB1) (Garg et al, 2013 ). Jin et al loaded chemotherapy DOX and photosensitive rose-bengal (RB) into ROS response micelles based on UCNPs (β-NaYF 4 :Yb,Er), and constructed the treatment nanoplatform (Jin et al, 2020 ). The ROS response micelles were constructed from biocompatible sialic acid (SA), PEG, thioketone (TK), and poly(lactic-co-glycolic acid) (PLGA).…”
Section: The Corpration Of Ucnps and Immunotherapymentioning
confidence: 99%
“…* p < 0.05; ** p < 0.01; *** p < 0.001. Copyright 2020, American Chemical Society (Jin et al, 2020 ).…”
Section: The Corpration Of Ucnps and Immunotherapymentioning
confidence: 99%